A New Multilateralism? A Case Study of the Belt and Road Initiative. (30th August 2020) - Zhou, Jingyuan
Abstract: The first five years (the first stage) of the Belt and Road Initiative (BRI) have drawn international attention and provoked scepticism and debate. This article explores questions about the nature of the BRI and its impact on multilateralism, which is increasingly fragile and under attack. After summarizing past practices employed in BRI investments, it analyses the characteristics of the BRI and assesses the results and implications. This article studies in depth one of the two primary BRI economic activities—special economic zones. The article introduces and compares the Asian Infrastructure Investment Bank and Chinese domestic banks in their respective financing practices and compares state-owned enterprises and privately owned enterprises in BRI practices. The article observes three characteristics from past BRI practices and analyzes their respective implications on the transformation of international trade governance. The first characteristic is the unconventional 'infrastructure development first, institution next' approach. The second is the plurilateral- and multilateral-focused method in international rule-setting processes. The third characteristic is innovation in the dispute settlement mechanism. Through a cautious examination, the article argues that experiences gained from BRI inform China's international rule-making efforts and further its domestic trade liberalization reform agenda, which will likely contribute to the convergence of rule-making in international trade.